Optimizing Air Compressor Productivity in Supporting Operational Activities on The Mt Ship. Gamalam - Naufal Annafi, Muhammad; Ala, Asman; Delta Susanto, Jarot (Green Publisher, 2023)
Air compressors are auxiliary machines on board that can produce high pressure air. This research was conducted because the productivity of the air compressor was less than optimal, causing air production and the performance of the air compressor to be less than optimal and disrupting operational activities on the ship. The impact that occurs when air production is reduced in the air compressor, the ship cannot operate according to the contract specified by the company, because the initial start of the main engine or main engine on board requires compressed air. Many factors can cause reduced production of air produced by air compressors, including the lack of performance of the suction valve and exhaust valve on the high pressure section which causes less maximum or longer time for filling air into the air bottle, low flow of the lubrication system on the piston which causes no compression to produce air. This research was carried out with the aim of identifying and analyzing the causes of the lack of performance of the suction and exhaust valves on high pressure sections and low flow of the piston lubrication system which results in less optimal performance of the air compressor when filling into air bottles. The method used in this study uses a qualitative descriptive method using primary and secondary data collection approaches and techniques. The lack of performance of the inlet and exhaust valves can be corrected by cleaning the carbon deposits on the valves and leveling the valve surfaces. The low flow of the lubrication system on the piston can be done by checking the lubricating oil pump, cleaning the lubricating oil filter, changing the lubricating oil periodically according to the instruction manual book, and adding lubricating oil according to the specifications of the air compressor.